2013
DOI: 10.1007/s00464-012-2769-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-emptive pregabalin on pain intensity and postoperative morphine consumption after laparoscopic cholecystectomy

Abstract: Administration of 600 mg pregabalin per os, divided in two preoperative doses, significantly reduces postoperative pain as well as opioid consumption in patients undergoing laparoscopic cholecystectomy, at the cost of increased incidence of dizziness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
2
24
1
7
Order By: Relevance
“…Chang et al [12] had also showed that pain scores, time for first rescue analgesia and additional need of ketolorac consumption did not differ significantly in pregabalin vs placebo. This is in contrast to other studies by Agarwal, Balaban, Sarakatsianou and Singh et al [7][8][9][10]. Bekawi et al had reported very different results than all previous studies [13].…”
Section: Opioid Consumptioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Chang et al [12] had also showed that pain scores, time for first rescue analgesia and additional need of ketolorac consumption did not differ significantly in pregabalin vs placebo. This is in contrast to other studies by Agarwal, Balaban, Sarakatsianou and Singh et al [7][8][9][10]. Bekawi et al had reported very different results than all previous studies [13].…”
Section: Opioid Consumptioncontrasting
confidence: 65%
“…Similarly, Balaban et al [8] showed decrease in pain scores with pregabalin 150 and 300 mg compared to placebo. Sarakatsianou in 2013 [9] demonstrated similar reduction in pain scores with 300 mg pregabalin administered twice before surgery. Singh et al in 2016 [10] also showed efficacy of 150 and 300 mg pregabalin in decreasing pain scores.…”
Section: Painmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the number of patients receiving rescue analgesic at various time intervals was found to be significantly less in pregabalin group compared to placebo group. Findings similar to our study are further supported by individual studies by Agarwal A et al (2008), 8 Balaban F et al (2012), 23 Sarakatsianou et al (2013) 24 and Singh TH et al (2014). 18 This is in contrast to a study by Peng et al (2010) 13 where they found that although 50 and 75 mg oral pregabalin were able to decrease pain scores in patients undergoing laparoscopic cholecystectomy, analgesic requirement in the form of fentanyl was not decreased.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have investigated the effectiveness of either pregabalin or celecoxib alone as a modifier of pain scores and opioid usage in laparoscopic surgery [14,[27][28][29][30][31][32][33][34][35][36][37][38][39]. Studies investigating celecoxib alone in laparoscopic surgery have generally shown positive results in decreasing pain intensity and opioid requirements postoperatively [27][28][29].…”
Section: Discussionmentioning
confidence: 99%